How Do You Feel Now? The Salience Network Functional Connectivity in End-Stage Renal Disease - Hu, Runyue; Gao, Lei; Chen, Peina; Wu, Baolin; Wu, Xiaoyan; Xu, Haibo (Frontiers in Neuroscience, 2020)
Objective: The network connectivity basis of cognitive declines in end-stage renal disease (ESRD) remains unclear. A triple-network model of salience (SN), executive control and default mode networks has been suggested critical for efficient cognition. Here, we aimed to test the hypothesis that SN may play a role in cognitive impairment in patients with ESRD. Materials and Methods: We investigated functional connectivity (FC) alterations within the SN between 43 ESRD patients (19 females/24 males, 46±10 years) and 43 healthy controls (HC) (19 females/24 males, 47±10 years), and performed linear support vector machine (LSVM) analysis on significant FC pairs within the SN to discriminate the two groups, and tested the accuracy of the classifier. Association and mediation analyses were conducted among the significant FC pairs within the SN nodes, clinical indicators, and neuropsychological tests scores. Results: We identified significant between-group FC pairs of SN and fairly good classification efficiency with significant accuracy (72.09%, p < 0.001). We found that FC between the right supramarginal gyrus and right anterior insula (AISL) was positively correlated with MoCA (r = 0.4010, p = 0.008); FC between dorsal anterior cingulate cortex (dACC) and left AISL was positively correlated with the level of hemoglobin (r = 0.4979, p < 0.001). Mediation analysis found that the indirect effect of hemoglobin on forward digit span test scores via the FC between dACC and right AISL (p < 0.05). Conclusion: Disrupted SN connectivity may help explain cognitive declines in ESRD patients and act as a potentially early biomarker. Moreover, the SN connectivity may interact with anemia to promote cognitive impairment.